A RE-EVALUATION OF THE BULBOUS IRISES - HALL, T.; TILLIE, N.; CHASE, W. (Annali di Botanica, 2000)
This paper examines the results of recent morphological and molecular studies on the bulbous irises. The following taxa are discussed: (1) subgenus Scorpiris and its relationship to the bearded irises and subgenus Nepalensis; (2) subgenus Xiphium and the Spuriae - Tenuifoliae alliance; (3) the reticulata irises and their links with the Syriacae.